Comparative Analysis of Electoral Trends in Pakistan and Bangladesh in the General Elections 2024 - Shah, Yawar Hayat; Azam, Maryam (Annals of Human and Social Sciences, 2025)
Electoral politics is a crucial aspect of a democratic society. Pakistan and Bangladesh, two significant states in the South Asian region, have both faced challenges in establishing a viable democratic system. The aim of the research is to examine the electoral trends and issue of electoral integrity in Pakistan and Bangladesh in General Elections. The 2024 General Elections in Bangladesh were marred by violent protests, leading to the opposition to question the legality of the elections. Similarly, the 2024 General Elections in Pakistan were met with questions about the fairness and transparency of the election results. Both countries have struggled with issues such as civil-military dissent, military rule, and weak democratic institutions, which have compromised the integrity of the electoral process. This study identified the main electoral trends in Pakistan and Bangladesh particularly in the General Elections 2024 to compare the state of democracy, role of opposition, civil-military relations, and youth participation in the electoral process.